Observation of biexcitons in the presence of trions generated via sequential absorption of multiple photons in colloidal quantum dot solids - Cihan, Ahmet Fatih (2013)
Multi exciton generation (MEG) and multi exciton recombination (MER) in semiconductor quantum dots (QDs) have recently attracted significant scientific interest as a possible means to improve device efficiencies [1-5]. Convenient bandgap tunability, easy colloidal synthesis, and solution-based processability of these QDs make them further attractive for such device applications using MEG and MER. For example, recent theoretical and experimental studies have shown that MEG enables >;100% peak external quantum efficiency where the generated multi excitons (MEs) are collected in a simple QD solar cell structure [1]. Furthermore, MEG has also been shown in QD photodetectors exhibiting substantially increased photocurrent levels [2]. Another promising application for MEs is the use of QDs as an alternative gain medium based on MER for lasers. Although MEG is very promising and supported with quite persuasive reports, there are still some debatable issues that need to be clarified. One of the issues that have generated great debates in the field has been the confusion of MER with the recombination of trions, which takes place in photocharged QDs. To utilize MEG and MER in practical devices such as QD solar cells and QD lasing devices, these phenomena need to be well understood. Here, we showed distinct spectrally-resolved temporal behavior of biexciton (BX), single exciton (X) and trion radiative recombinations in near unity quantum yield (QY) quasi-type II CdSe/CdS core/shell nanocrystal QDs. Upon sequential absorption of multiple photons, the extraction of Xs, BXs, and trions were achieved using time correlated single photon counting (TCSPC) measurements performed on low concentration thin film samples of these QDs at different emission wavelengths. The QDs were embedded in PMMA medium to obtain homogeneous samples and avoid Förster-type nonradiative energy transfer (NRET) between them. Here to extract Xs, BXs, and trions, we devised a new analysis approac- for the time decays of the QDs that allowed us to attribute the physical events to their corresponding time decay terms, which were further verified with their excitation intensity dependencies [6].